ANALISIS EFEKTIVITAS REKONSILIASI FISKAL TERHADAP KEPATUHAN PAJAK WAJIB PAJAK BADAN DI INDONESIA: STUDI PADA PERUSAHAAN JASA - Zahra Dinul Khaq; Rahayu Nugraheni Rachmawati; Puteri Anindya Maulan (Jurnal Akuntansi dan Bisnis, 2025)
Despite numerous tax reforms, corporate tax compliance in Indonesia’s service industry remains low. A key reason is the failure to reconcile financial accounting with tax regulations through fiscal reconciliation. This study analyzes the impact of fiscal reconciliation on corporate tax compliance among Indonesian service firms. A mixed-method approach was used: a quantitative survey of 120 service firms and qualitative interviews with 8 tax practitioners and stakeholders. Regression results (coefficient = 0.621, R² = 0.547) show a significant positive effect of effective fiscal reconciliation on tax compliance. Qualitative findings support this, highlighting key issues such as process complexity, limited understanding of tax laws, and a lack of technological infrastructure. These results contribute empirical insights to Indonesia’s tax literature, particularly for the service sector. The study’s novelty lies in positioning fiscal reconciliation as a strategic tool to enhance compliance. It offers practical policy suggestions, including digitalization of systems, improved human resources, and timely and accurate tax reporting mechanisms.